Contrast volume reduction using third generation dual source computed tomography for the evaluation of patients prior to transcatheter aortic valve implantation - Bittner, Daniel O.; Klinghammer, Lutz; Schuhbaeck, Annika; Hell, Michaela M.; Muschiol, Gerd; Gauss, Soeren; Lell, Michael; Uder, Michael; Hoffmann, Udo; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (European Radiology, 2016)
Chronic renal failure is common in patients referred for transcatheter aortic valve implantation (TAVI). CT angiography is recommended and provides crucial information prior to TAVI. We evaluated the feasibility of a reduced contrast volume protocol for pre-procedural CT imaging.Forty consecutive patients were examined with prospectively ECG-triggered high-pitch spiral acquisition using a novel third-generation dual-source CT system; 38 ml contrast agent was used. Image quality was graded on a visual scale (1-4). Contrast attenuation was measured at the level of the aortic root and at the iliac bifurcation.Mean patient age was 82 ± 6 years (23 males; 58 %). Mean attenuation/average image quality was 285 ± 60 HU/1.5 at the aortic annulus compared to 289 ± 74 HU/1.8 at the iliac bifurcation (p = 0.77/p = 0.29). Mean estimated effective radiation dose was 2.9 ± 0.3 mSv. A repeat acquisition was necessary in one patient due to image quality. Out of the 35 patients who underwent TAVI, 31 (89 %) patients had no or mild aortic regurgitation. Thirty-two (91 %) patients were discharged successfully.Pre-procedural CTA with a total of 38 ml contrast volume is feasible and clinically useful, using third-generation dual-source CT, allowing comprehensive imaging for procedural success.o Reduction of contrast agent volume is crucial in patients with chronic renal failure. o Novel third-generation computed tomography helps to reduce contrast agent volume. o Pre-procedural CT allows comprehensive imaging for procedural success before heart valve implantation. o A low-contrast CT protocol is feasible for pre-procedural TAVI planning.
EVALuna2:14600